Superconductivity from site-selective Ru doping studies in Zr5Ge3 compound - Sheng Li; Xiaoyuan Liu; Varun Anand; Bing Lv (New Journal of Physics, 2018)
Systematical doping studies have been carried out to search for the possible superconductivity in the transition metal doped Zr _5 Ge _3 system. Superconductivity up to 5.7 K is discovered in the Ru doped Zr _5 Ge _2.5 Ru _0.5 sample. Interestingly, with the same Ru doping, superconductivity is only induced with doping at the Ge site, but remains absent down to 1.8 K with doping at the Zr site or interstitial site. Both magnetic and transport studies have revealed the bulk superconductivity nature for Ru doped Zr _5 Ge _2.5 Ru _0.5 sample. The high upper critical field, enhanced electron correlation, and extremely small electron–phonon coupling, have indicated possible unconventional superconductivity in this system, which warrants further detailed theoretical and experimental studies.